Presse et délinquance ou comment lire entre les signes - Soubiran-Paillet, Francine (Criminologie, 1987)
Based on two newspapers published in different socio-political contexts, one in Nice, France, the other in Geneva, Switzerland, we would like to compare the way these two dailies view crimes against property. Does the journalist report theft, breach of trust or break and enter in the same way? Are the same variables used in the articles or are important changes made from one article to the other? If such is the case, who orders the changes in the structure of the articles? The work, which comprises a systematic list of six months daily articles, covers all typical situations published in the two newspapers. It seems, then, that the persons mentioned in the papers who belong to minority, as opposed to the majority groups, are generally presented as responsible for crime. It seems, too, that individuality disappears in the reconstruction of the reality by the media. All in all, the analysis shows that the press exercises only a relative influence on its readers.